Effects of mutations in acetate metabolism on high-cell-density growth of Escherichia coli - Contiero, Jonas [UNESP]; Beatty, C.; Kumari, S.; DeSanti, C. L.; Strohl, W. R.; Wolfe, A. (Nature America Inc, 2000)
To study the role played by acetate metabolism during high-cell-density growth of Escherichia coli cells, we constructed isogenic null mutants of strain W3100 deficient for several genes involved either in acetate metabolism or the transition to stationary phase. We grew these strains under identical fed-batch conditions to the highest cell densities achievable in 8 h using a predictive-plus-feedback-controlled computer algorithm that maintained glucose at a set-point of 0.5 g/l, as previously described. Wild-type strains, as well as mutants lacking the sigma(s) subunit of RNA polymerase (rpoS), grew reproducibly to high cell densities (44-50 g/l dry cell weights, DCWs). In contrast, a strain lacking acetate kinase (ackA) failed to reach densities greater than 8 g/l. Strains lacking other acetate metabolism genes (pta, acs, poxB, iciR, and fadR) achieved only medium cell densities (15-21 g/l DCWs). Complementation of either the acs or the ackA mutant restored wild-type high-cell-density growth, on a dry weight basis, poxB and fadR strains produced approximately threefold more acetate than did the wild-type strain. In contrast, the pta, acs, or rpoS strains produced significantly less acetate per cell dry weight than did the wild-type strain. Our results show that acetate metabolism plays a critical role during growth of E. coli cultures to high cell densities. They also demonstrate that cells do not require the sigma(s) regulon to grow to high cell densities, at least not under the conditions tested.
Keywords: acetate metabolism; acetate mutants; glucose-controlled high cell density fermentation; fed-batch fermentation; rpoS